2012
DOI: 10.1002/ptr.4746
|View full text |Cite
|
Sign up to set email alerts
|

Xanthorrhizol Induces Apoptosis Through ROS‐Mediated MAPK Activation in Human Oral Squamous Cell Carcinoma Cells and Inhibits DMBA‐Induced Oral Carcinogenesis in Hamsters

Abstract: Xanthorrhizol, a natural sesquiterpenoid compound isolated from Curcuma xanthorrhiza Roxb, has been known to inhibit the growth of human colon, breast, liver and cervical cancer cells. In this study, xanthorrhizol decreased cell viability, induced apoptosis and decreased the level of full-length PARP in SCC-15 oral squamous cell carcinoma (OSCC) cells. A decrease in cell viability and PARP degradation was not prevented by treatment with the caspase inhibitor Z-VAD-fmk in xanthorrhizol-treated cells. Xanthorrhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…Although patients received dental consultation prior to the initiation of radiotherapy, it still produced serious oral cavity problems that affect life quality [36]. Natural compounds have been preclinically and clinically investigated to be the chemopreventive or therapeutic agents for oral cancer [35, 37, 38]. Blister beetles are insects of family Meloidae , which contains about 2500 species, divided among 120 genera and 4 subfamilies (Eleticinae, Meloinae, Nemognathinae, and Tetraonycinae) [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Although patients received dental consultation prior to the initiation of radiotherapy, it still produced serious oral cavity problems that affect life quality [36]. Natural compounds have been preclinically and clinically investigated to be the chemopreventive or therapeutic agents for oral cancer [35, 37, 38]. Blister beetles are insects of family Meloidae , which contains about 2500 species, divided among 120 genera and 4 subfamilies (Eleticinae, Meloinae, Nemognathinae, and Tetraonycinae) [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, bioactive food components inducing apoptosis by ROS generation (Table 2) and other mechanisms play an emerging role in cancer therapy. According to other tumor entities several other natural compounds have been shown to activate ROS [58,61] in OSCC [77-81] and subsequent apoptosis in cancer cells and may therefore provide a clear rational to study them in further pre-clinical and clinical trials (Table 2). Moreover, phytochemicals [82] and vitamins have different hypoxia-inducible factor-1 (HIF-1) binding capacities (inhibitory activity: lycopene > curcumin > tocopherol > ascorbic acid) suggestive for their impact on the decrease in tumor hypoxia and antioxidative properties in normal tissue [83].…”
Section: Discussionmentioning
confidence: 99%
“…Its antitumor activity was higher than that of compound 2. However, compound 2 has been studied for a number of biological targets, notably for its antimicrobial [14][15][16][17][18] and anticancer [28][29][30][31][32][33][34][35][36] properties. In conclusion, this study has shown that the antibacterial capacity of C. xanthorrhiza is contained in the n-hexane fraction.…”
Section: Resultsmentioning
confidence: 99%